1996
DOI: 10.1590/s0004-282x1996000300011
|View full text |Cite
|
Sign up to set email alerts
|

Características sócio-econômicas de pacientes com acidente vascular cerebral

Abstract: RESUMO -Estudo de aspectos sócio-econômicos de 206 pacientes com AVC, atendidos no ambulatório de Doenças Neurovasculares no período de 1991 a 1992. Os principais achados foram: 23% dos pacientes apresentavam idade inferior a SO anos; o estado civil casado era significantemente mais frequente nos homens; 82% dos pacientes eram analfabetos ou semianalfabetos e 60% vivem com renda familiar de 1 a 2 salários mínimos. O impacto sócio-econômico causado pela instalação de um AVC em um membro da família é sempre gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
1
1
1
6
Order By: Relevance
“…Our sample was formed by a population who had low education level, agreeing with researches that had similar averages, showing that the Brazilian public service users present a low rate of schooling 14,16,17 . The low educational level and low socioeconomic status may influence the severity of aphasia in the early stage, and the illiterate present visuoperceptual difficulties hampering the intensity of recovery that may be low for people on that group 16,18 .…”
Section: Discussionsupporting
confidence: 70%
“…Our sample was formed by a population who had low education level, agreeing with researches that had similar averages, showing that the Brazilian public service users present a low rate of schooling 14,16,17 . The low educational level and low socioeconomic status may influence the severity of aphasia in the early stage, and the illiterate present visuoperceptual difficulties hampering the intensity of recovery that may be low for people on that group 16,18 .…”
Section: Discussionsupporting
confidence: 70%
“…A study conducted by Junior 25 , with healthy individuals, showed that men and women who had active sex life were married or had a regular partner, which shows a different profile compared with the post-CVA patients. The profile verified was also different from the findings by Santana et al 26 , in which there was a predominance of married men and women.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies 21,26,27 show that changes after CVA may result in sexual dysfunctions, such as: hypoactive desire, sexual aversion, impotence, premature ejaculation, orgasmic disorder, pain, discomfort after ejaculation, As to the characteristics of the sexual domains, most participants had regular partner (85.7%), reported difference in sex life after lesion (71.4%) and decreased sexual desire (64.3%) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…O estudo de Cavalcante et al [3] indicou maior prevalência de AVE no sexo feminino, atribuída à sobrevivência das mulheres até idades mais avançadas. Os estudos de Santana et al [22] e Silveira et al [15] encontraram maior proporção de jovens, sendo que no primeiro, tal fato foi atribuído às características do serviço onde a amostra foi selecionada. No presente estudo, acredita-se que a diferença não significante entre a faixa etária de homens e mulheres, deve-se ao fato de que as mulheres vêm adotando hábitos cada vez mais próximos daqueles antes adotados prioritariamente por homens, como por exemplo, etilismo e tabagismo; além do uso de anticoncepcionais, que também consiste em um fator predisponente ao AVE.…”
Section: Discussionunclassified
“…Com relação à escolaridade, os dados observados neste estudo mostram que a maioria dos pacientes avaliados possuía baixa escolaridade (ensino fundamental incompleto) ou era analfabeto, o que vai ao encontro da literatura [16,22]. A baixa escolaridade, muitas vezes associada à baixa renda e à dificuldade de acesso à informação, resulta em precariedade dos cuidados com alimentação e saúde, podendo levar a diversos comprometimentos, principalmente aqueles relacionados ao sistema cardiovascular, como infarto agudo do miocárdio e AVE.…”
Section: Discussionunclassified